IMPLEMENTATION OF CLASSROOM MANAGEMENT AND TEACHING STYLES IN ENHANCING THE EFFECTIVENESS OF ISLAMIC RELIGIOUS EDUCATION LEARNING IN PUBLIC SENIOR HIGH SCHOOLS IN BUTON REGENCY - Sufiani; Sumardona; Idil Adha (Academic Bright Collaboration, 2026)
This study aims to describe the implementation of classroom management and teachers’ teaching styles in enhancing the effectiveness of Islamic Religious Education (IRE) learning in public senior high schools in Buton Regency. This research employs a qualitative method with a descriptive approach. Data were collected through observation, interviews, and documentation. Data analysis involved three stages: data reduction, data display, and conclusion drawing. Data validity was ensured through triangulation, prolonged observation, and increased persistence. The findings show that effective classroom management involves organizing the classroom, enforcing rules, building positive relationships, understanding students’ backgrounds, mastering materials, and applying engaging and varied teaching methods with clear deadlines. Teachers adopt facilitator, demonstrative, collaborative, technology-based, personalized, and interactional styles. Supporting factors include curriculum, facilities, teachers, and students, while challenges arise from student issues, teacher limitations, and family background. This study contributes to improving classroom management and teaching strategies in IRE learning. However, it is limited to a specific regional context and qualitative design. This study highlights the integration of classroom management and diverse teaching styles in improving IRE learning effectiveness in a local educational context.